ØªØ·Ø¨ÙŠÙ‚ Ø£Ù„Ø¹Ø§Ø¨ ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ù†Ù…Ø§Ø°Ø¬ Ù‚ØµØ© Ù…Ø³Ù„Ø³Ù„Ø© ÙÙŠ ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù…: TATHBIQU ALâ€™ABI TAâ€™LIMIYATI NAMUDZAJI QISHSHOTI MUSALSALAH FI TANMIYATI MAHARAH AL-KALAM - Amirul Mukminin; Aisyatul Hanun; Sofyan Hamim (Lughatu Ad-dhat, 2023)
Maharatul kalam is one of the Arabic language skills that must be mastered by students, in learning there are many learning models and learning media, including language games using qishhoh musalsal, where students are expected to be able to speak / tell stories sequentially with the whole story. The purpose of this study was to analyze the application of learning games with the chain story model in improving Maharatul Kalam. The research method used is a descriptive qualitative approach with obesity data collection techniques as the main standard, then interviews to strengthen the results of observations and also documentation so that the data obtained is truly credible and valid. The results in the study were that students told stories using Arabic in sequence using a story ball thrown at one of the students as an opener to the story, then the ball was thrown at one of the other students and continued the story. And so on until the story is over.